2004
DOI: 10.1111/j.0956-7976.2004.00739.x
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Afrocentric Facial Features in Criminal Sentencing

Abstract: Prior research has shown that within a racial category, people with more Afrocentric facial features are presumed more likely to have traits that are stereotypic of Black Americans compared with people with less Afrocentric features. The present study investigated whether this form of feature-based stereotyping might be observed in criminal-sentencing decisions. Analysis of a random sample of inmate records showed that Black and White inmates, given equivalent criminal histories, received roughly equivalent se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

31
423
4
6

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 488 publications
(464 citation statements)
references
References 16 publications
31
423
4
6
Order By: Relevance
“…The response scale ranged from 1 (Not at all [trait term]) to 9 (Extremely [trait term]). In all behavioral studies (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14), each face was visible until the participant responded, the interstimulus interval (ISI) was 1,000 ms, and the order of faces was randomized for each participant.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The response scale ranged from 1 (Not at all [trait term]) to 9 (Extremely [trait term]). In all behavioral studies (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14), each face was visible until the participant responded, the interstimulus interval (ISI) was 1,000 ms, and the order of faces was randomized for each participant.…”
Section: Methodsmentioning
confidence: 99%
“…For example, ''thieves are notable for their expressive faces and manual dexterity, small wandering eyes that are often oblique in form, thick and close eyebrows, distorted or squashed noses, thin beards and hair, and sloping foreheads'' (2). Lombroso provided his ''scientific'' testimony at several criminal trials.Although modern science, if not folk psychology (3), has largely discarded such notions, trait evaluations from faces predict important social outcomes ranging from electoral success (4-6) to sentencing decisions (7,8). Studies show that people rapidly evaluate faces on multiple trait dimensions such as trustworthiness and aggressiveness (9, 10).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although competence does not seem relevant in evaluating whether a person might be willing and able to do harm, people use competence-cues from the faces of two opponents to judge who will win an election (Willis & Todorov, 2006). Similarly, a study investigating real sentencing decisions as a function of the degree of Afrocentric facial qualities found that more pronounced Afrocentric facial cues result in harsher sentencing (Blair, Judd, & Chapleau, 2004). These findings suggest that raters make very context-specific judgments based CHANGING THE PERSONALITY OF A FACE 7 on faces and they agree in doing so, even if these judgments do not fit the 2D space of face evaluation.…”
Section: Context-specific Judgments Based On Facesmentioning
confidence: 99%
“…These inferences occur spontaneously and rapidly (Ballew & Todorov, 2007;Bar, Neta, & Linz, 2006;Rule & Ambady, 2008a; Todorov, Pakrashi, & Oosterhof, in press; Willis & Todorov, 2006). Furthermore, recent evidence suggests that these impressions impact the decisions that people make in a variety of important domains, including mate choice , politics (for reviews of this literature see: Hall, Goren, Chaiken, & Todorov, 2009; Olivola & Todorov, in press), business/finance (Gorn, Jiang, & Johar, 2008;Naylor, 2007;Pope & Sydnor, 2008;Ravina, 2008;Rule & Ambady, 2008b), law/forensic-science (Blair, Judd, & Chapleau, 2004;Eberhardt, Davies, Purdie-Vaughns, & Johnson, 2006; Zarkadi, Wade, & Stewart, in press;Zebrowitz & McDonald, 1991), and the military (Mueller & Mazur, 1996).A crucial question, then, is whether appearance-based inferences are valid forms of social judgment. That is, can we use appearances to determine a target-person's characteristics, or are we being fooled by first impressions?…”
mentioning
confidence: 99%